Prison Overcrowding as a Limitation in the Transformation of Incarcerated Individuals - Rojas Víquez, Mónica (2023)
The following work is part of the project A UNA's Pedagogy for Reunion: Human rights, transformative education, and literature in institutional care centers in Costa Rica, from the National University of Costa Rica, from the Institute of Latin American Studies (IDELA). This aims to observe the prison as an anthropological site where individuals living in these contexts, typically overcrowded, encounter restrictions on their freedom of choice and autonomy, which impacts their transformation process.